L’industriel automobile et l’alcool : Limite des stratégies multinationales au Brésil - Duquette, Michel (Études internationales, 1983)
In the Third World, the Energy Crisis of 1973 emphasized the vulnerability of certain large oil-importing countries engagea in an extensive process of industrialization. As the multinational-dominated automobile industry represented the core of the recent industrializing profile in Brazil, the end of Growth meant a direct threat to its future development as an energy-consuming economic sector. A powerful lobby was then activated to intervene on the side of the State and the national bourgeoisie. The latter was putting forward the PRO-ALCOOL program in the Mid-Seventies, as a response to the new challenge. An alliance with the car industry was made possible when the State withdrew from a tradition of direct involvment in Energy (exemplified by PETROBRAS), to enhance the private sector. Such a neo-liberal strategy in oil-substitution would be aimed at a potentially unlimited market in South America and the Carribean for alcohol-powered cars, while being essentially dependent upon the performance of its participants : the national bourgeoisie engagea in agro-business, and the automobile industry.In the light of recent findings from a research conducted in Brazil, the author recognized the originality of this internationalizing strategy, in the context of regional market integration. However, given its neo-liberal nature, it is not surprising that controls (of costs and quality) remained largely ineffective. Further structural limitations, such as technological deficiencies caused by inadequate R & D activities, uneasy relations among actors, especially among multinational corporations themselves, and a lack of private funding (to be related to the deep crisis in Latin America) delayed the implementation of the program in its original conception. Although reluctant to the introduction of new competitors, especially from Japan, the multinational could be forced into a new alliance that goes far beyond the actual loose formula, if they want the PRO-ALCOHOL program to be reactivated in the near future.